Long-term trends and patterns in ultra-processed food consumption among Korean adults from 1998 to 2022 - Hyeseung Lee; Yesol Yim; Yerin Cho; Jiyeon Oh; Soeun Kim; Yejun Son; Hyesu Jo; Seohyun Hong; Masoud Rahmati; Hanseul Cho; Jiyoung Hwang; Dong Keon Yon (Scientific Reports, 2025)
Abstract Ultra-processed foods are linked to adverse health outcomes, making it crucial to monitor consumption trends. Despite rising consumption due to Westernized diets in Asia, long-term studies targeting Asian adults are lacking. Thus, we analyzed ultra-processed food consumption trends among Korean adults from 1998 to 2022. Additionally, we compared intakes before and during the pandemic to evaluate the potential impact of the COVID-19 pandemic. Furthermore, we compared the nutrient profiles of ultra-processed and non-ultra-processed food group intakes. This study used data from the Korea National Health and Nutrition Examination Survey (KNHANES) from 1998 to 2022, classifying food into four NOVA groups. Dietary intake was assessed In 2020–2022, ultra-processed foods had a higher proportion using a single 24-hour recall for 96,447 individuals aged 20 years or older. Sampling weights were applied to adjust for the complex survey design and non-responses. We calculated the weighted means and confidence intervals for the proportion of energy intake by NOVA food groups and various nutrient profiles. The proportion of energy intake from ultra-processed foods among Korean adults steadily increased from 17.41% in 1998–2005 to 26.71% in 2016–2019 (mean difference: 9.30% [95% CI, 8.62–9.98%]), but declined for the first time during the pandemic, falling to 25.33% (mean difference: -1.39% [95% CI, -2.18% to -0.59%]). In 2020–2022, ultra-processed foods had a higher proportion of calories from carbohydrates (62.12% vs. 58.81%) and fats (28.22% vs. 22.31%) but a lower proportion from protein (10.32% vs. 17.26%) compared to non-ultra-processed foods. From 1998 to 2022, the fat content of both ultra-processed and non-ultra-processed foods significantly increased, rising from 26.24 to 28.15% for ultra-processed foods (mean difference: 1.91% [95% CI, 1.33–2.49%]) and from 16.81 to 22.26% for non-ultra-processed foods (mean difference: 5.45% [95% CI, 4.99–5.91%]). This study examined 25-year trends in ultra-processed food consumption among South Koreans, showing a consistent increase in energy intake from ultra-processed foods until the COVID-19 pandemic, during which it declined for the first time. However, this decline may be temporary, underscoring the need for sustained efforts to reduce ultra-processed food consumption.